Pauline Ethics-Based Character Education Management Model for Building Effective Paulinian Schools toward SDG 4: Quality Education - Layu Marsiana; Erny Roesminingsih; Karwanto Karwanto (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to develop a Pauline Ethics-Based Character Education Management Model for building effective Paulinian schools and supporting SDG 4, particularly Target 4.7 on quality education. Method: A qualitative case study was conducted at Santo Paulus Junior High School, Kuala Kapuas, Central Kalimantan, Indonesia. Data were collected through in-depth interviews, participant observation, and document analysis involving the principal, teachers, educational staff, students, parents, and school documents. Data were analyzed through data reduction, data display, and thematic conclusion drawing. Results: The findings indicate that the values of Regularité, Simplicité, and Travail are internalized through learning activities, role modelling, habituation, mentoring, reflection, and school culture. These processes contribute to the formation of Paulinian character, including discipline, responsibility, humility, perseverance, integrity, and service orientation. The internalization of these values further strengthens Paulinian school culture and supports the development of an effective school environment. Novelty: This study proposes a Pauline Ethics-Based Character Education Management Model that integrates educational management, value internalization, character formation, school culture, and school effectiveness within a single conceptual framework. The model demonstrates that school effectiveness is influenced not only by academic and administrative factors but also by the successful management of ethical values and school culture.